THE EFFECT OF WORK FROM HOME (WFH) ON THE PRODUCTIVITY OF EDUCATORS IN THE PUBLIC ELEMENTARY SCHOOL ENVIRONMENT OF PEJATEN BARAT JAKARTA - Sulaiman, Angga; Adawiyah, Roudhotul (International Peneliti Ekonomi, Sosial dan Teknologi, 2020)
During the pandemic all fields have undergone a shift in working methods and in the world of education itself the method of work done by educators is to change the learning method from the previous one in the classroom by being done face-to-face transformed into a method of learning remotely (PJJ) online and in their ownhomes. The method used is Quantitative Method by using Descriptive approach is a type of research where later form of explanation or description more regularly, logically, arranged neatly and also clearly from the beginning until the completion of the research process. The results showed that working in WFH has several advantages and disadvantages for all educators in the state elementary school environment, especially those located in the west pejaten village of Jakarta.